Evaluating the Role of School-Based Physical Activity in Mitigating Cardiometabolic Risk Factors in Children and Adolescents with Overweight or Obesity: A Systematic Review and Meta-Analysis - Dingmeng Mao; Bowen Li (Children)
Background: Overweight or obese children and adolescents have a higher risk of developing cardiometabolic health problems compared with their healthy-weight peers, which are likely to progress to cardiovascular disease and are associated with a range of negative impacts. Objectives: To evaluate the effects of school-based physical activity (PA) interventions on cardiometabolic risk factors in children and adolescents with overweight or obesity. Method: A search of online databases was conducted to identify relevant studies up to 31 January 2025. Results: Eleven studies were included, involving 963 participants aged 7 to 18 years. School-based PA interventions have a significant effect size (ES) in reducing body fat percentage (ES = −0.43, p < 0.01), diastolic blood pressure (ES = −0.27, p < 0.05), triglycerides (ES = −0.38, p < 0.01), fasting blood glucose (ES = −0.60, p < 0.01), blood insulin (ES = −0.62, p < 0.01), and homeostatic model assessment-insulin resistance (ES = −0.58, p < 0.01) in overweight or obese students. However, no significant improvements were observed in body mass index, body mass index z-score, waist circumference, waist-to-height ratio, maximal oxygen consumption, systolic blood pressure, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and total cholesterol. Conclusion: School-based PA interventions lasting 6 weeks longer, twice a week or more, can significantly mitigate some cardiometabolic risks of overweight or obese children and adolescents. Effective, targeted PA programs should be considered in the school setting to promote the cardiometabolic health of this vulnerable group.